Reproductive Biology of the Coyote (Canis latrans): Integration of Mating Behavior, Reproductive Hormones, and Vaginal Cytology - Carlson, Debra A. (J Mammal, 2008)
The reproductive biology of wild Canis species is often described as unique among mammals because an unusual combination of behavioral and physiological characteristics including a seasonally monestrous cycle, copulatory lock or tie, obligatory pseudopregnancy, social monogamy, and biparental care of the young. We investigated social behavior, endocrine profiles, and vaginal cytology of female coyotes (Canis latrans) during 4 breeding seasons, 2000–2003. Blood levels of estradiol, progesterone, prolactin, and relaxin were measured, and mating behavior and changes in vaginal epithelium were documented. After aligning the data from each individual to her estimated day of ovulation, we compared pregnant coyotes with nonpregnant females and evaluated temporal relationships among hormone levels, behavior, and vaginal cytology. We found that patterns of proceptive and receptive behaviors correlated with the secretion of steroid hormones, as did vaginal epithelial cytomorphosis. In addition, although progesterone levels of pregnant and pseudopregnant coyotes were indistinguishable, prolactin demonstrated a discernible intergroup difference and relaxin was only detectable in pregnant females. Although this study included characteristics not previously published for this species, it also showed how key aspects of reproduction were correlated temporally, and emphasized the importance of an integrated perspective when addressing the reproductive biology of coyotes, or other wild species of canids.